2018
DOI: 10.21475/ajcs.18.12.08
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Seed germination depends on internal and external factors relating to the seed but the whole process will normally occur if there are no restrictions during the stages of germination. So, the aim of the present study was to evaluate the viability and the vigor of pitaya seed under different pH levels. A completely randomized design was employed under a 3 × 13 factorial design [pitaya genotypes: Hylocereus undatus (white pitaya); H. undatus x H. costaricensis (pitaya hybrid I), and H. costaricensis x H. undatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Very high content of EC and exchangeable Na of the soil might not suitable for sugarcane because high salt content in soil cause inhibition of growth, chlorophyll synthesis, PEPC ase activity, and decreased the uptake of K + and Ca ++ ions of sugarcane (Joshi & Naik, 1980). In addition, Cruz, da Costa Ferreira Júnior, & dos Santos (2018) found that Na accumulation declined plant growth and elevated electrolyte leakage with destruction to the photochemical part of photosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Very high content of EC and exchangeable Na of the soil might not suitable for sugarcane because high salt content in soil cause inhibition of growth, chlorophyll synthesis, PEPC ase activity, and decreased the uptake of K + and Ca ++ ions of sugarcane (Joshi & Naik, 1980). In addition, Cruz, da Costa Ferreira Júnior, & dos Santos (2018) found that Na accumulation declined plant growth and elevated electrolyte leakage with destruction to the photochemical part of photosynthesis.…”
Section: Resultsmentioning
confidence: 99%